USULAN PERBAIKAN SISTEM MANAJEMEN KESELAMATAN KERJA MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESMENT CONTROL (HIRAC) DI PT PERKEBUNAN NUSANTARA IV - Uun Novalia Harahap; Abdul Azis Syarif; Yetti Meuthia Hasibuan; Jekson Priadi Pasaribu; Diah Elliza Carolina Hutabarat (Jurnal Simetri Rekayasa, 2022)
Occupational Safety and Health (K3) protects the safety and health of employees in carrying out their work, and strives to control all forms of potential hazards that exist in the work environment of PT. The Tea Factory Unit of Nusantara Plantation, Tobasari Plantation, is part of PTPN IV which operates in the argo industry. The main product to be processed is the. PTPN IV Tobasari Tea Factory Unit is a very risky work environment. In the factory production process, it is also not far from risks such as large fires. During the production of PTPN IV, the Tobasari unit needed an occupational safety program to develop employee creativity so that the quality and production results of the company were good. The method used in this study was to use the Hazard Identification and Risk Assessment Control (HIRAC) method. Hazard Identification identifies potential hazards that may occur, and the next step is Risk Assessment Control, namely assessing risks based on likelihood and Severity. The results showed that there were 12 potential hazards identified and categorized in 3 risk ratings, of which 5% were included in high risk, 26% were in moderate risk, and 19% were in low risk.